PERFORMANCES OF DENIAL AND REFUSAL:: CASA T* BELOW AND BEYOND THE COLONIAL REPRESENTATIONAL NEUROSIS - Belo, Pollyane; Gonçalves, Fernando (Contemporanea, 2022)
This paper discusses the principle of denial that characterizes and underpins the colonial cistem to reflect on escape possibilities. Its starting point was the ban suffered in 2021 by Casa T* (a welcoming space for travestis and trans individuals, racialized people and immigrants in Lisbon, Portugal) in the organization of the city’s LGBTQI+ March, without any prior request for participation in the event on their part. Considering the physical and symbolic dimensions of an anticipated refusal of a desire that did not even come to be, the writing was driven by the following questions: what are the bases of representational thinking that denies and performs the abandonment of bodies and people and disregards their desires and existences? How can we think of escape routes that allow plural constructions outside the colonial representational neurosis? Episteme worlds derived from radical black and trans* radical thought helped us to draft answers to such questions that stem from the mentioned episode and, at the same time, encompass fundamental queries of political representation outside the modern Subject.